2004
DOI: 10.2202/0027-6014.1390
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of New Student Campus Recreation Centers

Abstract: The student recreation center (SRC) at many colleges and universities has evolved from being a place to lift weights and take aerobics classes to becoming a high-powered recruitment tool (Colleges use recreation, 2002). The present study included the development of an instrument to assess the use and impact of SRCs. Students (N = 655; users = 537, nonusers = 118) were surveyed about their use of and satisfaction with their university's newly constructed SRC. The overall findings revealed that a majority of SRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 0 publications
3
29
2
Order By: Relevance
“…Most students reported living either on-campus or off-campus within one mile of the university. The data from this research is fairly consistent with results from prior studies (Watson et al, [2006]; Zizzi et al, [2004]; Miller et al,[2008]). We can suggest that users are more likely to be male, Caucasian, non-smokers, live on-campus or off-campus within a mile of the college or university, age 21 and under, not involved in any type of extracurricular activity, and have no health concerns.…”
Section: Summary Conclusion and Future Directionssupporting
confidence: 89%
See 3 more Smart Citations
“…Most students reported living either on-campus or off-campus within one mile of the university. The data from this research is fairly consistent with results from prior studies (Watson et al, [2006]; Zizzi et al, [2004]; Miller et al,[2008]). We can suggest that users are more likely to be male, Caucasian, non-smokers, live on-campus or off-campus within a mile of the college or university, age 21 and under, not involved in any type of extracurricular activity, and have no health concerns.…”
Section: Summary Conclusion and Future Directionssupporting
confidence: 89%
“…These numbers represent a dramatic drop in physical activity within the transition period from high school to college life. In a recent study on the impact of new campus recreation centers by Zizzi, Ayers, Watson, & Keeler (2004), it was reported that rates of physical activity in the United States have not improved over the last 20 years regardless of significant funds spent on educational and informational programming (Buckworth, 2000;Dishman, 1994;USDHHS, 2000).…”
Section: Obesity and Lack Of Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Providing recreational programmes is critical to the overall development of mankind and often provides a vehicle to the overall educational engagement and academic achievement (Nichlos, 2007). These recreation programmes offered and the campus recreation facilities are considered as key components of a student's decision to attend a certain institution (Haines, 2001, Zizzi et al, 2004, Scott, 2014. The programmes are often intellectualized as providing a site for self-control and character building (Hartmann, 2003).…”
Section: Introductionmentioning
confidence: 99%